KARAKTERISTIK KOMUTER DAN KUALITAS HIDUP - M Fitri Rahmadana (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2014)
This study aimed to examine whether there are differences in quality of lifefor commuters based on the characteristics of the respondents.The research was conducted by an experimental approach using primarydata. Samples were taken as 384 respondents in proportional random samplingwith snowball sampling method. Analysis of the data are t-test and F-test.The results showed no difference in quality of life for commuters by sex,age, marital status and occupation, while there were no differences by education.